Bentuk Dan Kategori Khazanah Ekoleksikal Pengetahuan Obat Tradisional Suku Yali Papua: Kajian Ekolinguistik - Wandik, Eduard (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2017)
This paper aims to express about the ecological interactions and human in forming a system of language (linguistic) as the embodiment ofhuman concrete and the environment for trying to highlight, analyzeand present all the elements in the universe so that the interactions that take the place within it, required a description of ecology and ecosystems in ecological context or eco-linguistic language for Yali tribe in Papua Province at Yalimo regency on Tangumsili Village of Apahapsili District.The fact that the environment is now seen as a let nature is preserved. Preservation of environmental resources is closely related to Yali language preservation because the eco-lexical treasure is part of the natural situation relating to civilized of Yali human on the environment.In the practices, the results of this paper topic aboutâEco-Lexical TreasureKnowledge of Traditional Medicine of YaliTribe: EkolinguistikTheoricalâ is expected to provide insight to the native speakers community about the importance of preserving the environment associated with traditional medicines of Yali tribe as the natural resource as characteristic peculiarities realized through language. In addition, the results of this research thesis can be expected to make as a local content lesson that illustrate the richness of language and culture that can be utilized by the world of education, as formal and informal so that future generations understand and love of the Yali language, Yali culture and Yali natural environment.